Enhancement in the optical and electrical properties of CdS thin films through Ga and K co-doping. (15th March 2017) - Yılmaz, S.; Töreli, S.B.; Polat, İ.; Olgar, M.A.; Tomakin, M.; Bacaksız, E.
Abstract: In the presented work, Ga-doped CdS and (Ga-K)- co -doped CdS thin films are grown on glass substrates at a temperature of 400 °C through spray pyrolysis. Influence of K-doping on structural, morphological, optical and electrical characteristics of CdS:Ga thin films are examined. K level is changed from 1 at% to 5 at% for CdS:Ga samples just as Ga concentration is fixed 2 at% for all CdS thin films. It is observed from the X-ray diffraction data that all the samples exhibit hexagonal structure and an increase level of K in Ga-doped CdS samples causes a degradation in the crystal quality. Energy-dispersive X-ray spectroscopy measurements illustrate that the best stoichiometric film is acquired when K content is 2 at% in Ga-doped CdS films. Optical transmission curves demonstrate that CdS:Ga thin films exhibit the best optical transparency in the visible range for 4 at% K content compared to other specimens. A widening in the optical bandgap is unveiled after K-dopings. It is obtained that maximum band gap value is found as 2.45 eV for 3 at%, 4 at% and 5 at%. K -dopings while Ga-doped CdS thin films display the band gap value of 2.43 eV. From photoluminescence measurements, the most intensified peak is observed in the deep level emission after incorporation of the 4 at% K atoms. As for electrical characterization results, the resistivity reduces and the carrier density improves with the increase of K concentration from 1 at% to 4 at%. Based on all the data, it can be deduced that 4 at% K-doped CdS:Ga thin films show the best optical and electrical behavior, which can be utilized for solar cell devices.